1983
DOI: 10.1111/j.1365-2273.1983.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous papillomas of the larynx in adults. A review of 63 cases

Abstract: Sixty-three cases of squamous papillomas of the larynx occurring in adults are presented. Twelve cases started as juvenile papillomas and continued into adult life. Twice as many males as females were in the series. The papillomas were always present on the true vocal cords at presentation, although other parts of the larynx were involved to a variable extent. The symptom of hoarseness gave a good indication as to the state of the larynx during treatment. Malignancy did not develop in patients with papillomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
2
37
1
Order By: Relevance
“…However, 75% of these patients were females with chronic juvenile-onset laryngeal papillomatosis. Adultonset laryngeal papillomatosis is a disease with a 2±4-fold male predominance [12,13], and the present study found no difference in HPV antibodies between male patients and controls.…”
Section: Discussionmentioning
confidence: 41%
“…However, 75% of these patients were females with chronic juvenile-onset laryngeal papillomatosis. Adultonset laryngeal papillomatosis is a disease with a 2±4-fold male predominance [12,13], and the present study found no difference in HPV antibodies between male patients and controls.…”
Section: Discussionmentioning
confidence: 41%
“…The rare condition of malignant transformation of papillomas is considered to occur mainly in irradiated patients or in those with long-standing tobacco abuse [17]. The percentage of malignancies developing in RRP patients varied in previous series from 0% to 22% [1,15]. In our series, the rate of airway carcinoma was 4.6%.…”
Section: Classification Clinical Course and Malignancymentioning
confidence: 56%
“…Capper et al suggested that papillomas appearing as 'heaped up, keratotic, lesions' should be excluded, as they would represent a premalignant lesion and are histologically characterized by the absence of fine finger-like processes and the presence of dysplasia [15]. This series reported on histological evidence of moderate dysplasia in papillomas of 25 patients, in which 52% were encountered as multiple RRP after the removal of papillomas without cellular atypia.…”
Section: Classification Clinical Course and Malignancymentioning
confidence: 90%
“…Papilloma is a benign exophytic neoplasm of epithelium on a connective tissue core1. Respiratory papillomatosis (RP) is a benign disease characterized by unregulated growth of wartlike neoplasms of the larynx, trachea, and bronchi with propensity for recurrences (RRP).…”
Section: Introductionmentioning
confidence: 99%